Study on Suture Tensile Properties of Polyimide Composites for Flexible Solar Wings - JIAO Yunlei; GUO Chenliang; FENG Shixu; WU Yuemin; ZUO Yangjie (工程科学与技术)
Polyimide fiber fabric composite laminate is a typical aerospace flexible film material. High quality joining of those film composites was challenging, and the joining quality has an importance influence on the service performance of spacecraft. In order to improve the joining performance of those film composites, the sewing connection method of polyimide fiber fabric composite laminate was investigated in this paper, which was used in flexible solar wing blanket surface of spacecraft. The sewing test of polyimide fiber fabric composite laminate was designed to evaluate the sewing quality of the joint. Bothe the tensile failure progress and final failure modes were characterized by quasi-static tensile tests. Here, the surface tensile deformation of the specimen was evaluated by a digital image correlation (DIC) measurement technology. Moreover, the parameter test of film sewing joints was also conducted to understand the influence of sewing parameters on the connection performance, including the sewing dislocation and sewing stitches. Finally, the tensile slip performance of the specimen was accessed by tensile slip test, in which different sewing parameters were also considered. During the test, the adhesive layer peeling, surface cracking, or fiber peeling in the sewing area were examined.The tensile load-displacement results showed that the tensile failure process of the sewing joint of polyimide fiber fabric composite material laminate exhibited a linear growth characteristic in the force displacement curve. Both the composite material laminate and the sewing joint were in an elastic deformation state. Then the failure strength was reached causing multiple failure modes in the joint. The parameter study indicated that the highest average value of the maximum tensile load of the specimen was observed corresponding to the suture stitch length of 4 mm. Moreover, it was found that the shorter the suture stitch length, the higher the average maximum tensile load value. This was most likely due to that the shorter suture stitches leaded to the increasing of the number of joining holes, when the sewing length was the same. When the specimen was loaded, the load distribution of the suture zone was observed to be more uniform. At the same time, the local maximum stress level of the joining hole decreased, which in turn delayed the tensile failure of the suture area. For the perspective of two-line dislocation specimens, it was observed that the 50% dislocation could obtain a larger average maximum tensile load value than that of 25% dislocation. This was likely due to that the dislocation could change the local stress distribution around the suture hole. At the same time, it also improved the joining interaction relationship of the specimen lead to the changing of the load transfer condition.The tensile loading progress of the specimen was showed that, due to the stress concentration carried by the sutures, the surface of the whole specimen was severely wrinkled. Before the tensile failure occurred, the surface of the specimen has been wrinkled due to the local stress concentration of the connecting hole. In addition, the suture zone was observed to have the weakest carrying capacity. This was due to the transverse tow being carried through the resin in the tensile direction. For this reason, a large number of tows were stretched and peeled off. Moreover, the adhesive layer on the surface of the suture area was also destroyed. It was worth noting that the fiber tow peeling only occurred in the suture area, and the stress concentration of the suture joint was the main reason. At the same time, the tensile failure resistance in other areas was significantly better.At the initial stage of loading, the local strain at the end of the seam was the largest, and the local surface adhesive layer was destroyed soon. With the increase of external load, the local strain around the suture stitch further increased. The glue layer in the suture zone was destroyed. Subsequently, the fiber bundles in the suture zone were peeled and further exacerbated. Eventually, the fiber bundles in the suture area were completely peeled off, and the suture joint was completely separated and failed. In the tensile failure process, the failure modes of the specimens under different parameters were similar. However, it was worth noting that when the stitches were sutured at 8 mm, all the specimens were pulled off at both ends of the suture area, except for the wrinkles and transverse fiber bundle peeling. The main reason for this was probably that the stitches were too long, and the suture holes under the same load conditions were subjected to greater local loads. In particular, the sutures at both ends of the suture bearing area were relatively less restrictive, and the suture pull-off eventually occurred.Further analysis of the displacement of the specimen perpendicular to the surface was conducted. It was showed that the specimen had obvious and varying wrinkles during the loading process. At the beginning of loading, no wrinkles occurred on the surface of the specimen. However, when the load further increased, obvious wrinkles occurred on the surface of the specimen. And the wrinkle direction protruded in the direction of shooting. Subsequently, the folds intensified, and the middle area remained convex in the direction of the shot, but the edges were concave backwards. Finally, the degree of wrinkling reached a maximum and was further reduced by the destruction of the specimen during subsequent loading.The tensile slip test showed that the tensile slip of the specimen under all suture parameters was less than 0.2 mm, and the suture area exhibited good stiffness. At the same time, the number of stretches increased, the slip mean value showed a weak upward trend, and the suture zone showed signs of stiffness degradation. After tensile loading, there were no occurrences of adhesive layer peeling, surface cracking, or fiber peeling in the sewing area, whether on the front or back sides of specimens. It was indicated that the sewing connection method showed high reliability and stiffness in polyimide fiber fabric composite structures joining. This study can be useful in designs of the aircraft thin wall composite structures joining.